2017
DOI: 10.1097/ncm.0000000000000233
|View full text |Cite
|
Sign up to set email alerts
|

Validating Performance of a Hospital Discharge Planning Decision Tool in Community Hospitals

Abstract: The value of systematically proactive approaches to discharge planning is increasingly recognized, but establishing the performance capacity of support tools is critical for optimizing benefit. These study findings support use of the ESDP in regional community hospitals, making it a useful, open-source decision support tool for various health care delivery systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Seven articles, all of which reported studies that evaluated the ESDP tool's use for adults, remained and were included in this literature review. 14,[17][18][19][20][21][22] Results from the critical appraisal of the included studies' methodological quality using the CASP Checklist for Cohort Studies are shown in Table 2. Using the planned quality rating approach, 5 studies 14,[17][18][19][20] were rated as being of "good" methodological quality, and 2 studies 21,22 were rated as "fair.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven articles, all of which reported studies that evaluated the ESDP tool's use for adults, remained and were included in this literature review. 14,[17][18][19][20][21][22] Results from the critical appraisal of the included studies' methodological quality using the CASP Checklist for Cohort Studies are shown in Table 2. Using the planned quality rating approach, 5 studies 14,[17][18][19][20] were rated as being of "good" methodological quality, and 2 studies 21,22 were rated as "fair.…”
Section: Methodsmentioning
confidence: 99%
“…A primary limitation noted across the 7 included studies was a lack of population diversity. 14,[17][18][19][20][21][22] Four of the included studies reported on participant race, 17,[19][20][21] and in those studies, the proportions of participants who were categorized as White ranged from 76.7% to 99.5%. Other reported race categories included African American/Black (0.83%-14%), Hispanic (0.83%-1.3%), and other (2.55%-9.3%), with each of these race categories representing less than 14% of participants in any 1 of the 4 studies.…”
Section: Methodsmentioning
confidence: 99%
“…Holland et al showed that older age, walking limitation, living alone before admission, and the level of disability indicate the need for a specialized discharge planning team in surgery units. 8,[29][30][31] A specialized discharge planning team may also be of value in the management of cancer patients. 7 Indeed, discharge is often delayed by the lack of a suitable care facility.…”
Section: Benefits and Tools For Discharge Planning Teamsmentioning
confidence: 99%
“…4,5 Studies of surgical and neurology wards have shown that older age and poor functional independence are risk factors for transfer to PAC. [6][7][8][9] Specific tools [7][8][9][10] have been developed to identify patients at risk of transfer to PAC and it has been shown that the use of some of these tools is associated with a shorter length of hospital stay. 9,11 Acute geriatric units (AGUs) provide specific care for frail, dependent or multimorbid older adults with acute health problems.…”
Section: Introductionmentioning
confidence: 99%
“…In order to facilitate and improve the discharge process and to prevent undesirable outcomes, different interventions involving ICT solutions have been developed over the years. Different decision-supportive tools [ 9 , 10 ], tailormade discharge models and structured discharge summaries [ 11 13 ] have been tested with various results. A review of statistics published between 1999 and 2016 show that 7–89% of the ICT projects in different sectors failed because they did not meet one or more of three basic criteria: finishing on time, finishing within budget, and achieving satisfactory results [ 14 ].…”
Section: Introductionmentioning
confidence: 99%